Mesenchymal stromal cells cultured in physiological conditions sustain citrate secretion with glutamate anaplerosis - Giuseppe Taurino; Ruhi Deshmukh; Victor H. Villar; Martina Chiu; Robin Shaw; Ann Hedley; Engy Shokry; David Sumpton; Erica Dander; Giovanna D'Amico; Ovidio Bussolati; Saverio Tardito (Elsevier, 2022)
Bone marrow mesenchymal stromal cells (MSCs) have immunomodulatory and regenerative potential. However, culture conditions govern their metabolic processes and therapeutic efficacy. Here we show that culturing donor-derived MSCs in Plasmax™, a physiological medium with the concentrations of nutrients found in human plasma, supports their proliferation and stemness, and prevents the nutritional stress induced by the conventional medium DMEM. The quantification of the exchange rates of metabolites between cells and medium, untargeted metabolomics, stable isotope tracing and transcriptomic analysis, performed at physiologically relevant oxygen concentrations (1%O2), reveal that MSCs rely on a high rate of glucose to lactate conversion, coupled with parallel anaplerotic fluxes from glutamine and glutamate to support citrate synthesis and secretion. These distinctive traits of MSCs shape the metabolic microenvironment of the bone marrow niche and can influence nutrient cross-talks under physiological and pathological conditions.